Experiencers at the syntax-pragmatics interface. The case of the jo ‘I’ – construction in Catalan - Espinal, M.Teresa; Cyrino, Sonia (Glossa (London), 2025)
This paper aims to support the thesis that Speech Act related operators have landing sites in syntax, specifically at the syntax-pragmatics interface. In order to attain this goal, it presents the first formal analysis of a construction, dubbed the jo ‘I’ – construction, that shows an overt first person strong pronoun sitting in sentence-initial position of declarative sentences both in pro-drop and partial pro-drop languages of the Romance family. Taking Catalan as a case in point, it is shown that, prosodically, this first person strong pronoun has a particular intonation (a rising pitch accent followed by a high boundary tone). Syntactically, it corresponds not to a subject but to a (kind of) hanging topic that requires a resumptive element in the clause, while semantically it introduces a reference to the speaker who at the time of uttering the sentence is performing a subjective declaration speech act.